A qualitative screening and quantitative measurement of organic contaminants on different types of marine plastic debris. (November 2015) - Gauquie, Johanna; Devriese, Lisa; Robbens, Johan; De Witte, Bavo
Highlights: Extensive list of organic compounds found on marine plastic debris identified. Validated method for PAH and PCB determination on beached pellets. Beached pellets reveal distinct pollutant pattern compared to sediment and biota. Abstract: Chemical compounds present on plastic were characterised on different types of plastic litter and beached pellets, using a general GC–MS screening method. A variety of plastic related compounds, such as building blocks, antioxidants, additives and degradation products, were identified next to diverse environmental pollutants and biofilm compounds. A validated method for the analysis of PAHs and PCBs on beached pellets at the Belgian Coast, showed concentrations of ∑ 16 EPA-PAHs of 1076–3007 ng g −1 plastic, while the concentrations of ∑ 7 OSPAR-PCBs ranged from 31 to 236 ng g −1 plastic. The wide variety of plastic compounds retrieved in the general screening showed the importance of plastic as a potential source of contaminants and their degradation products.